Diagnostic investigation, intervention, and outcome for post-subtotal gastrectomy patients who present with jaundice - Wang, Duan; Zhu, Liang; Kong, Fanyi; Pan, Yingyu; Liu, Wei; Wang, Xuan; Pan, Weidong; Cao, Jian; Xu, Qiang; Wu, Dong (Frontiers in Medicine, 2025)
PurposeEndoscopic retrograde cholangiopancreatography (ERCP) is a useful diagnostic and interventional tool in patients with obstructive jaundice. In patients who had subtotal gastrectomy, however, the implementation of ERCP has become more difficult. This study aims to investigate the accuracy of contrast-enhanced CT, MRI/MRCP and PET/CT in lesion localization, characterization, and extent evaluation in post-subtotal gastrectomy patients who present with obstructive jaundice. The interventional methods for biliary drainage, their success rate and patient outcome were also investigated.MethodsElectronic medical records were reviewed to identify patients hospitalized for obstructive jaundice at Peking Union Medical College Hospital, who had previously undergone subtotal gastrectomy. The clinical information, imaging and interventional examination data of those patients were retrospectively collected.ResultsBetween 2018 and 2023, 36 patients with previous subtotal gastrectomy were hospitalized for ob-structive jaundice at our hospital. The majority of lesions were malignant, including 19 gastric cancer recurrence (47.5%), and 12 other malignancies (30.0%). Benign lesions included inflammatory biliary stricture, biliary stones, and IgG4-related disease. The three imaging modalities had similar performance in lesion localization and characterization, whereas PET/CT showed higher accuracy compared to MR and CT in detecting extensive disease (92.8% vs. 83.3% vs. 60.0%). Percutaneous transhepatic cholangial drainage was applied more frequently than ERCP and surgery (69.4% vs. 25.0% vs. 5.5%), and there was no significant difference concerning technical and clini-cal success rate and complication.ConclusionGastric cancer recurrence and newly-developed pancreaticobiliary malignancies were the main causes of obstructive jaundice in patients who had subtotal gastrectomy. PET/CT was superior to MRI/MRCP and contrast-enhanced CT in determining lesion extensiveness. Percutaneous transhepatic cholangial drainage (PTCD) was the preferred method for managing obstructive jaundice. Despite the effectiveness of interventions, a significant number of patients experienced short-term disease progression.